CLINICAL AND EPIDEMIOLOGICAL ASPECTS OF PRIMARY IMMUNODEFICIENCY DISEASES (PID) AND EARLY DIAGNOSIS OPTIONS - I. A. Korsunskiy (Medicinskaâ Immunologiâ, 2017)
Neonatal screening for primary immunodeficiencies (PID) provides a unique opportunity for early detection of moderate to severe immune disorders. Thus, the patients could be provided with best available therapy, due to effective treatment according to updated PID management guidelines. Clinical outcomes of recently implemented screening programs have demonstrated high sensitivity and specificity of the diagnostic techniques used and good survival rates. The existing evidence provides a strong basis for inclusion of PID screening into general Russian neonatal screening program.